A New Model for Portal Protein Profile Analysis in Course of Ileal Intraluminal Bile Acid Infusion Using an In Situ Perfused Rat Intestine - Montagnani, Marco; Tsivian, Matvey; Neri, Flavia; Ben Zvi, Ido; Mantovani, Irina; Nanni, Paolo; Benevento, Marco; Simoni, Patrizia; Marangoni, Antonella; Pariali, Milena; Fato, Romana; Bergamini, Christian; et al. (Medicinal Chemistry, 2011)
Due to the importance of intestinal transport in pharmacological studies and the emerging role of intestinal signalling activity in the gut-liver axis, we have developed a new method to investigate intestinal transport and liver signalling using cell and serum free mesenteric perfusion system in the rat. The method regarding bile acid active absorption was validated, then, the portal venous content was examined for fibroblast growth factor 15(FGF15), a putative signalling protein produced by the ileal enterocytes following bile acid absorption. After isolation and cannulation of the relevant vessels (abdominal aorta and portal vein), the abdominal aorta and the terminal ileum were infused with respectively Krebs-Ringer solution and tauroursodeoxycholate (TUDCA) and the absorption was assessed by its recovery in the portal vein. After immunoblot, liquid chromatography and mass spectrometry analysis were performed both on gel bands digestion products and on portal outflow samples in order to evaluate if negligible amounts of FGF15 were present in the portal circulation. TUDCA absorption was efficient, intestinal morphology and oxygen consumption were normal. Despite accurate analysis, we could not find FGF15. Our method proved to be reliable for studying the active bile acid absorption. It is also suitable to identify molecules produced by enterocytes and transferred to the portal circulation in response to absorption of different substances such as nutrients or drugs. Since FGF15 was not recovered we suggest the possibilities that this protein is produced in very little amounts, poorly transferred outside the cell, or that it is extremely unstable and rapidly degraded.
Keywords: enterocyte oxygen consumption